Effect of Backlash on Transient Processes in System with Distributed Parameters - G. S. Lenevskij; К. V. Ovsiannikov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper demonstrates a new model of mechanical part of a system with distributed parameters. The model takes into account a backlash in a coupler and an effect of elastic moment of resistance. Using a method of limiting transition an adequacy of the given model is shown in comparison with one-mass model.